China syndrome : the true story of the 21st century's first great epidemic - Greenfeld, Karl Taro, 1964- (New York, NY : Harper Perennial, 2007)
When SARS broke out in January 2003, author Greenfeld was the editor of Time Asia in Hong Kong, just a few miles from the epicenter of the outbreak. After vague, initial reports of terrified Chinese emptying pharmacy shelves and boiling vinegar to'purify' the air in nearby Guangdong province, Greenfeld and his staff soon found themselves immersed in the story of a lifetime. His scientific thriller takes readers on a ride that blows through the Chinese government's effort to cover up the disease. Greenfeld tracks this mysterious killer outbreak, from the bedside of one of the first Chinese victims to overwhelmed hospital wards crashing from the onslaught of cases, from cutting-edge labs where researchers struggle to identify the virus to the war rooms at the World Health Organization headquarters in Geneva.--From publisher description.
Includes bibliographical references and index.
Keywords: SARS (Disease) -- China -- History; Avian influenza -- China -- History